Animal Manure on Grassland and Fodder Crops. Fertilizer or Waste? 1987
DOI: 10.1007/978-94-009-3659-1_7
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of excreted nitrogen by grazing cattle and its effects on sward quality, herbage production and utilization

Abstract: Abstract. Grazing cattle exert positive and negative effects on pasture production. It is shown that at a fertilizer nitrogen (N) input of 200 kg N ha -I yc 1 and more, the benefit from N circulation through urine and dung is not of significance for the pasture as a whole. Of the negative effects, poaching has the greatest influence on the response of pasture production to N fertilization.Two one-year experiments are described which showed that there were no significant differences in the response of grassland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
1
2

Year Published

1992
1992
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 13 publications
4
82
1
2
Order By: Relevance
“…Such behaviour during daylight would also follow from our almost reciprocal patterns during daylight and night time resulting from the avoidance of areas with high excrement density during grazing. Cattle reject for a period of time herbage growing near dung patches (Hirata et al 1987;Lantinga et al 1987Lantinga et al , 1995Marten and Donker 1964). Schnyder et al (this volume) also observed that herbage removal was less in the areas of excrement accumulation despite a large amount and quality of herbage.…”
Section: Influence Of Site Propertiesmentioning
confidence: 97%
“…Such behaviour during daylight would also follow from our almost reciprocal patterns during daylight and night time resulting from the avoidance of areas with high excrement density during grazing. Cattle reject for a period of time herbage growing near dung patches (Hirata et al 1987;Lantinga et al 1987Lantinga et al , 1995Marten and Donker 1964). Schnyder et al (this volume) also observed that herbage removal was less in the areas of excrement accumulation despite a large amount and quality of herbage.…”
Section: Influence Of Site Propertiesmentioning
confidence: 97%
“…Data on dietary factors affecting hippuric acid concentration are rather scarce. Lantinga et al (1987) showed considerable diurnal variation in hippuric acid concentrations in urine of grazing cows, with lowest proportions (fraction of total N) between 0600 and 1200 h, and highest between 1800 and 2400 h. Cow urine hippuric acid concentration was lower with low-CP diets compared with high-CP diets (Kreula et al, 1978). Upon increased maturity of grass, contents in grass of CP and aromatic acid precursors decreased and that of lignin increased, whereas the hippuric acid excretion in urine decreased (Martin, 1970).…”
Section: Urea In Urinementioning
confidence: 99%
“…Intensive grazing, mainly by cattle, is found in medium to high population density areas, mostly in temperate climate zones of Europe, North and South America and, increasingly, in the humid tropics. In both extensive and intensive grazing systems, substantial N losses may occur through leaching and volatilisation from point sources of urine and faeces where N concentrations may exceed the equivalent of 200 and 2000 kg N/ha, respectively (Lantinga et al, 1987).…”
Section: Manure Management Practices -A Global Viewmentioning
confidence: 99%
“…Intensive grazing, mainly by cattle, is found in medium to high population density areas, mostly in temperate climate zones of Europe, North and South America and, increasingly, in the humid tropics. In both extensive and intensive grazing systems, substantial N losses may occur through leaching and volatilisation from point sources of urine and faeces where N concentrations may exceed the equivalent of 200 and 2000 kg N/ha, respectively (Lantinga et al, 1987).If livestock production is partly or completely based on confined animal feeding, manure is normally collected and must be managed from the time of excretion, during storage, possibly by treatment, and finally during spreading to land (Chadwick et al, 2011), although in some regions a Lagoons are typically earthen sedimentation basins for dilute waste from housed animals; sludge is degraded anaerobically, while the liquid evaporates or is pumped to spray fields. Liquid manure/slurry typically has a higher dry matter content and may include bedding material and is stored in tanks and may form a crust during storage.…”
mentioning
confidence: 99%